THE EXPERIENCE OF A COMBINED VACCINE AGAINST DIPHTHERIA, PERTUSSIS, TETANUS, POLIO AND HAEMOPHILUS INFLUENZAE TYPE B IN HEALTHY CHILDREN AND CHILDREN WITH VARIOUS DISABILITIES - O.A. Rychkova; N.V. Kazakevich; N.P. Sennikova; D.S. Chemakina (Union of pediatricians of Russia, 2011)
An open clinical observation over a period of post-vaccination in 184 children (ages 3 to 18 months), vaccinated and re-vaccinated with the combined vaccine against diphtheria, pertussis, tetanus, polio and Haemophilus influenzae type b using the standard procedure. Period of observation was 2009-2010, age of children - 3-4.5-6-18 months. All vaccinated children were divided into 3 groups: I - healthy, II - with allergic diseases, III - with CNS pathology. The features of post-vaccination period in each group have been determined. The general and local vaccination reactions, as in various manifestations and on terms have been evaluated. A combined vaccine demonstrated a good tolerance in healthy children included in the study, as well as in children of a risk group.Key words: diphtheria, pertussis, tetanus, polio, Haemophilus influenzae type b, immunization, combined vaccine, post-vaccination period, post-vaccination reactions, children.